Conflict Among Groups of Students: A Case Study of Langowan 3 State Junior High School - Sumolang, Nortje (JR Education, 2023)
This research was conducted at SMP Negeri 3 Langowan and focused on managing the conflict among students. It could be described as follows: (1) the types of conflict between groups of students, (2) how the strategies of the headmaster in managing the conflict. This investigation used a qualitative approach. The techniques of collecting data were: (1) observation, (2) interview, (3) document study, (4) and compilation of the three techniques (triangulation). The research instruments were the researcher herself, field notes, and interview guidelines. The obtained data was analyzed by following: (1) coding, (2) data reduction, (3) data display, (4) data verification, and then the data verification, was done as follows: (a) credibility, (b) transferability, (c) dependability. Based on data analysis, the findings were as follows: 1. The types of conflict among 14 groups of students: (1) a group of clever students insulted then a group of less clever students, (2) another group of students was playing gane the other group of students interrupted the play, (3) different opinion in discussion among groups of students, (4) one student in a group attack a student in another group caused conflict between the groups, (5) conflict between groups because one student of the group moved into the other group. 2. Based on research funding, most teachers at SMP Negeri 3 were interviewed, and according to them, the funding results were true. The strategies used by the headmaster to handle the conflict among groups of students are (a) trust to solve the problem to the teacher who became picket, (b) if it was not solved then trust it to OSIS, (c) and then to the special teacher, counselor, (d) and then the lost, would be solved by the headmaster by using problem-solving approached.